Surgical Site Infection after Craniotomy in Neuro-Oncology (SINO): A protocol for an international prospective multicentre service evaluation across the United Kingdom and Ireland. - Keng Siang Lee; Balint Borbas; Daoud Chaudhry; Ashvin Kuri; Lawrence Best; Conor S Gillespie; Hakim-Moulay Dehbi; Kristian Aquilina; Paul Brennan; Puneet Plaha; Keyoumars Ashkan; Michael D Jenkinson; et al. (PLoS ONE)
Introduction Given its proximity to the central nervous system, surgical site infections (SSIs) after craniotomy (SSI-CRAN) represent a serious adverse event. SSI-CRAN are associated with substantial patient morbidity and mortality. Despite the recognition of SSI in other surgical fields, there is a paucity of evidence in the neurosurgical literature devoted to skin closure, specifically in patients with brain tumors. The primary objective of this service evaluation is to ascertain the incidence and the risk factors associated with SSI-CRAN. The secondary objectives would be a) to ascertain the incidence of SSI-CRAN in sutured versus stapled wounds, after accounting for patient, surgical and hospital confounders of SSI-CRAN and b) to determine the percentage of patients with gliomas that begin adjuvant oncological treatment in patients with infection versus those without infection. Methods Surgical Site Infection after Craniotomy in Neuro-Oncology (SINO) is a international prospective multicentre service evaluation that will include patients with an intracranial neoplasm, both primary and secondary neoplasms, treated with cranial surgery (including biopsy). Consecutive paediatric (<18 years) and adult (≥18 years) patients diagnosed with a brain tumour, undergoing cranial surgery between 1st October 2024 and 1st December 2024 will be included. Prospective data will be collected with a follow-up of 90 days.